2022
DOI: 10.3389/frai.2022.903077
|View full text |Cite
|
Sign up to set email alerts
|

The interactive reading task: Transformer-based automatic item generation

Abstract: Automatic item generation (AIG) has the potential to greatly expand the number of items for educational assessments, while simultaneously allowing for a more construct-driven approach to item development. However, the traditional item modeling approach in AIG is limited in scope to content areas that are relatively easy to model (such as math problems), and depends on highly skilled content experts to create each model. In this paper we describe the interactive reading task, a transformer-based deep language m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…As an example, Figure 1 describes the automated content generation process with human‐in‐the‐loop used in the Duolingo English Test (Attali et al., 2022). Human experts stay in the loop of construct definition, task design, item generation, and refinement to review item quality, fairness, and bias.…”
Section: Llm Generative Ai and Human‐centered Aimentioning
confidence: 99%
“…As an example, Figure 1 describes the automated content generation process with human‐in‐the‐loop used in the Duolingo English Test (Attali et al., 2022). Human experts stay in the loop of construct definition, task design, item generation, and refinement to review item quality, fairness, and bias.…”
Section: Llm Generative Ai and Human‐centered Aimentioning
confidence: 99%
“…Similarly, Attali et al. (2022) used GPT‐3 to create interactive reading passages involving human reviewers. Bezirhan and von Davier (2023) also sought expert opinions to assess the quality of the texts generated with GPT.…”
Section: Text Analysis Cognitive Modelmentioning
confidence: 99%
“…Von Davier (2018) carried out a study examining automatically generated items through an online survey and used experts' opinions for the validation. Similarly, Attali et al (2022) used GPT-3 to create interactive reading passages involving human reviewers. Bezirhan and von Davier (2023) also sought expert opinions to assess the quality of the texts generated with GPT.…”
Section: Text Analysis Cognitive Modelmentioning
confidence: 99%
“…This issue is, for example, illustrated by Shi and Aryadoust’s (2022) systematic review of automated writing evaluation (AWE) systems, which concluded that domain definition inferences are underrepresented in AWE research. Similarly, even the most sophisticated automatic item generation (AIG) systems (e.g., Attali et al, 2022), while making great advances, are currently still trained on more “traditional,” “conventional” language use, and restricted in the kind of tasks (input and questions) they can produce (as well as continuing to require considerable human reviewing). Thus, a challenge for future work on technology in language testing and assessment will be to reflect the progress made in (applied) linguistics regarding the nature of language and language use in society, and to prioritize construct operationalization insights, in order to avoid restricting domain representation through technology-mediated testing.…”
Section: Looking Aheadmentioning
confidence: 99%